Research of Power-shift Control of High-powered Tractor Under Load Condition - Xia Guang; Shi Xinxin; Tang Xiwen; Zheng You; Sun Baoqun (Jixie chuandong)
Aiming at constant torque output,the constant-torque control strategy of power-shift is proposed. Based on constant-torque control strategy,considering diesel engine speed characteristics and the practical needs of tractor under load condition,the practical control strategy of power-shift is proposed for high-powered tractor. The power-shift process is divided into two periods,which are speed synchronization period and power transfer period respectively. Power transfer period comes first and speed synchronization period comes later when power-shift-up,while speed synchronization period comes first and power transfer period comes later when power-shift-down. Based on the two periods of power-shift,the relationship between actuating pressure of oncoming and off-going clutches and the principles for upper-limit of actuating pressure during power-shift are presented. Based on MATLAB/Simulink,power-shift process is modeled and simulated. The results show that the practical power-shift control strategy can realize no power break and large consistent torque output during shift without coordinating engine,so that the high-powered tractor can adapt to the changes of working resistance and operate continuously without stopping,which improves operation efficiency.